Review of Literature of Canna indica and its Potential Use as an Antiviral Agent for COVID-19 - Harpreet Kaur; Smriti Bahl; Dhanashri R. Patil; Rajan Keshri (International Journal for Research in Applied Sciences and Biotechnology, 2021)
Plants are irrefutably the most promising natural resource used in the treatment of various ailments since ages. In the ongoing pandemic situation, it would be beneficial to develop a cure to combat corona virus using such natural resources. There is an exigent need to come up with a non-invasive and effective treatment over vaccines to fight the coronavirus. Natural treatments are the best alternative to pharmaceutical drugs, which may damage the host and cause various adverse side effects. The plant Canna indica consists of phytochemicals such as flavonoids, alkaloids and terpenoids which may aid in the development of a potential antiviral agent in the future. The ongoing research and the widespread application of flavonoids, alkaloids and terpenoids mainly, have shown their effectiveness against the SARS covid 19 virus. Further, preclinical trials must be conducted on the phytochemicals present in Canna indica which may prove to be a promising factor in future. This article aims to provide information required to explore and claim the antiviral properties of the plant against SARS-COV. The phytochemicals flavonoids, alkaloids and terpenoids present in C. indica have significant antiviral properties that can potentially help humanity fight this virus. Thus, it is essential to broadly study Canna indica for further research aspects.